Interrogations - Språkbanken Text (University of Gothenburg, 2024)
The corpus is protected, contact Ylva Burman (ylva.byrman@svenska.gu.se) for more information and access.

Korpusen är skyddad, kontakta Ylva Burman (ylva.byrman@svenska.gu.se) för mer information och åtkomst.
Förhör
Keywords: Language Technology (Computational Linguistics); corpus; Natural Language Processing; Språkbehandling och datorlingvistik